In vitro cytocompatibility evaluation of poly(DL-lactic acid) scaffolds loaded with minocycline and voriconazole addressing osteomyelitis - Zegre, Miguel (2021)
Purpose: In this work is proposed the cytocompatibility evaluation of an innovative system based on the dual delivery of minocycline (Min) and voriconazole (Vor), aiming for bone infection therapeutics.